Applying Semantic Search and Large Language Models to Solve Assortment Gaps in E-Commerce - Tran, Ngoc Khiem; Zamazal, Ondřej; Chudán, David; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis addresses the problem of assortment gaps in e-commerce, with a particular focus on the grocery retail sector. The main objective is to develop a robust and scalable solution for identifying missing or substitute products by leveraging semantic search techniques and large language models (LLMs).
Vedoucí práce: Ondřej Zamazal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analytics [obor bakal. práce]; bakalářské práce; bachelor's theses